Isolation and molecular identification of fungi in bananas with and without leaf spots - Mogollón-Farias, César Augusto (2026)
Introduction. The foliar structure of banana plants is a determining factor in the development and yield of the crop, making the microbial composition present in leaf spots relevant for understanding the emergence and spread of diseases. Objective. To isolate and molecularly identify fungi in bananas with and without leaf spots. Materials and methods. A non-experimental study with a quantitative approach and descriptive level was conducted. Banana leaves from Musa acuminata (cv. IC2) with spots (HCM) and without spots (HSM) were collected from a conventionally managed agricultural plot located in Pampas de Hospital, Tumbes, Peru, in May 2019. Leaf fragments of 5 × 5 mm were cultured on microbiological media, and fungal strains were isolated and characterized based on their macrostructures. DNA was extracted from the strains, and conventional PCR targeting the ITS region of fungi (700 bp) was performed. The PCR products were sequenced using the Sanger method in double strands. Taxonomic assignments at the species level were made using the BLAST tool, based on homology comparison with sequences from GenBank. Results. A total of eleven fungal species were identified in HCM and eight in HSM, including both phytopathogenic and non-phytopathogenic species. The predominant species in HCM were Fusarium spp., Cladosporium cladosporioides, and Lasiodiplodia theobromae. Additionally, HCM shared three genera with HSM: Nigrospora, Cladosporium, and Fusarium. Conclusions. The isolation and molecular identification of fungi in bananas with and without leaf spots allowed the identification of phytopathogenic and beneficial species.